Hubungan Asupan Energi dan Status Gizi terhadap Kelelahan Kerja pada Sopir Bus Toraja-Makassar - Yanti, Putri; Asna Ampang Allo (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2024)
Fatigue is believed to be a common problem often encountered by workers, including bus drivers. Fatigue is caused by various factors such as energy intake and nutritional status. This study aims to determine the relationship between calorie intake and nutritional status in Toraja-Makassar bus drivers. This type of research is analytical observational with a cross sectional study approach. The total sample of 35 people was taken using total sampling technique. Data was collected using a questionnaire to measure work fatigue, food recall to obtain energy intake data and Body Mass Index to obtain nutritional status data. The data obtained was processed using the SPSS program. The results showed that there was a relationship between energy intake (p=0.027) and nutritional status (p=0.007) with work fatigue. The conclusion of this study is that energy intake and nutritional status are related to work fatigue in Toraja-Makassar bus drivers.